Pengaruh Pengalaman Pelanggan Herbalife Ciamis Pada Pembelian Ulang - Nurfatwa, Sri; Hendi Sobari (JURNAL EKONOMI PERJUANGAN, 2024)
How customer experience influences repeat purchases of Herbalife Ciamis is the subject of this research. This research used a quantitative descriptive method with 35 respondents. The data used is primary and secondary. Simple regression analysis is used as an analytical tool. The research results show that: 1. Herbalife Ciamis Customer Experience shows a score of 2,215 in the interval 2,058 to 2,450, which is in the very good classification; 2. Repurchase shows a score of 1,258 in the interval 1,176 to 1,400, which is in the very good classification; and 3. The influence of customer experience on repeat purchases at Herbalife Ciamis has a significant influence with a value of 30.4 percent. Apart from that, other factors contribute